Inaugural speech by the Vice-Chancellor at the installation of the Chancellor and my own installation as Vice-Chancellor of Midlands State University - 17 March 2001 - Bhebe, Ngwabi M. (Midlands State University, 2017)
Inaugural speech by Professor Ngwabi Bhebe, Vice Chancellor, Midlands State University, Zimbabwe